Seeds of Control : Japan's Empire of Forestry in Colonial Korea - Fedman, David (Book collections on Project MUSE., 2020)
"This study of Japanese "forest reclamation" in Korea during the period of Japanese colonial rule (1895-1945) holds the notion of conservation up for scrutiny, examining the roots of Japanese practices and ideas about the Korean landscape as well as the consequences and aftermath of the Japanese approach to "greenification" in Korea. The Japanese program for natural resource management included change in how woodland ownership rights were controlled at both the national and village level as well as efforts to change how Koreans cooked and heated their homes and to inculcate "forest love thought" among the Korean people, and culminated with an extreme increase in extraction during the Second World War. This project offers a compelling environmental approach to Korean history but also expands environmental thinking about Japan into colonized lands and contributes to broaderconversations about colonial forestry globally"--